MELAWAN DOMINASI PENGUASA: WACANA DEMOKRASI DELIBERATIF UNTUK INDONESIA - Asmaul Husna (SOURCE : Jurnal Ilmu Komunikasi, 2019)
Almost twenty one years Indonesia escape from the clutches from the regime of Orde Baru, in fact this nation does not necessarily become a democratic nation. The concept of citizenship embodied in the fourth principle of Pancasila which should interpreted as a citizen of the owner of supreme sovereignty in a country, it misinterpreted into objects which is influenced by the wisdom of the authorities, and the implementation of democracy is run solely limited to compliance with the rules and not within the framework to empower citizens. In the middle uncertainty of finding the ideal form of democracy, appear discourse on deliberative democracy which emphasizes the active participation of citizens through the media and the vocal organizations to play a very significant influence in the process of establishing the legal and political policies. If we explored it more deeply, this idea looks similar to the idea of Democracy of Pancasila which was popularized by the founding fathers of Indonesia. Offering a more humanistic approach, egalitarian, and accommodating this idea seems quite interesting if it actually implemented in Indonesia.Keyword: Citizens, Deliberative, Democracy, Participation.